Penerapan Green Product Pada Usaha Kuliner : Sebuah Tinjauan - Malihah, Lola; Ahsanunnida, Ruhama; Haryanto, Dwi (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2025)
Globalization and technological advancements have brought many changes and innovations to various products. One of the sectors that has experienced a lot of progress and change is the economic sector. Many business actors innovate the products they offer. This article is a literature review that aims to analyze the application of green products in the culinary sector. This sector was chosen considering that it is related to food and beverages which are basic needs. Data was obtained from sharing literature sources in the form of books, research results and articles published in scientific journals. The findings show that culinary business actors can implement green products from upstream to downstream. This application can be started by using raw materials that are safe for consumer health and friendly to the environment. Furthermore, when packaging for the distribution process, packaging materials that are safe for health and natural materials can be used. And in the downstream part, it also pays attention to the residue or waste from production activities. So that it does not have an impact on health and environmental sustainability